The Implementation of Boarding School System in Forming Students' Spiritual Attitude - Luthfiyana, Mela; Suhono, Suhono; Nufus, Hayatun; Lestari, Ayu; Rahmawati, Sri Tuti (Tapis: Jurnal Penelitian Ilmiah, 2021)
This aim of article was to analyze the system boarding school at SMA International Islamic High School (IIHS) Jakarta, and the implementation of boarding system school in forming the spiritual attitude of students in school. The research method used qualitative research by using a descriptive approach. The data sources and secondary data sources. The data collection method in this research used observation, interviews, and documentation. Method of data analysis by means of data collection, data education, data display and drawing conclusions or verification. The result showed that the implementation of the boarding school system in shaping student’s spiritual attitudes through that delivery of Islamic Studies material as Islamic knowledge and daily worship habits such as praying 5 times in congregation, reading dzikir, learning Al-Qur’an. Keywords: Boarding School System, Students’ Spiritual Attitude, Spiritual Attitude